Do pregnant people have opportunities to participate in clinical trials? an exploratory survey of NIHR HTA-funded trialists - Rebekah Burrow; Lisa Hinton; Mike Clarke (Trials)
Abstract Background Pregnant people are often excluded from clinical trials, primarily due to safety concerns. However, exclusion causes population-level harms as well as sometimes providing individual protection. Harms caused to pregnant people by exclusion from clinical trials have been clearly evidenced and highlighted during the COVID pandemic. The National Institute for Health and Care Research (NIHR) has since provided guidance on improving inclusion of under-served groups, which includes pregnant people, in clinical research. Appropriate inclusion and active facilitation to participate are required to provide equitable evidence-based healthcare during pregnancy and to comply with ethical principles for research. Methods We carried out an exploratory, online, cross-sectional survey of trialists to assess whether, why, and how pregnant people are included or excluded from clinical trials funded by the NIHR Health Technology Assessment (HTA) Programme, with awards starting in 2022–2023. Trialists were the respondents, with trials the primary focus of this survey. Invitations were sent to trialists between October 2023 and March 2024. Summary statistics were calculated to describe the characteristics of the trials and respondents, to describe eligibility of pregnant people, reasons for this, and how this eligibility is documented and implemented. Results We identified 120 trials of which 88 were eligible for this survey. Responses were received for 81 trials. Pregnant people are excluded from 34 of these 81 trials. Pregnant people are eligible for inclusion in 40 of the 81 trials, including four which partially exclude people during pregnancy. Eligibility is unclear for seven trials. Exclusions are mostly for safety reasons. Sponsors and regulatory authorities are unnecessary barriers to inclusion in some trials. Eight trials of 40 trials make explicit or deliberate attempts to include people during pregnancy. Conclusions A minority of the 120 trials include people during pregnancy. Most trials for which pregnant people are eligible do not report explicitly including people during pregnancy or facilitating their inclusion. A small number of trials, different in setting, clinical area, and intervention type, are intentionally designed and conducted in a way that include people during pregnancy. There are clear opportunities to improve the inclusion of pregnant people in clinical trials in the NIHR HTA Programme.